2003
DOI: 10.1074/jbc.m300064200
|View full text |Cite
|
Sign up to set email alerts
|

Central Role of a Serine Phosphorylation Site within Duck Hepatitis B Virus Core Protein for Capsid Trafficking and Genome Release

Abstract: Viral nucleocapsids compartmentalize and protect viral genomes during assembly while they mediate targeted genome release during viral infection. This dual role of the capsid in the viral life cycle must be tightly regulated to ensure efficient virus spread. Here, we used the duck hepatitis B virus (DHBV) infection model to analyze the effects of capsid phosphorylation and hydrogen bond formation. The potential key phosphorylation site at serine 245 within the core protein, the building block of DHBV capsids, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
42
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 37 publications
5
42
0
Order By: Relevance
“…1 and 2 (see Materials and Methods), the putative unstable mature NCs formed by the mutant core proteins, which might have been accumulated in the cells, could have been eliminated as a result of the nuclease digestion. This possibility was supported by previous studies by us and others showing that certain capsid mutations of DHBV can indeed lead to preferential destabilization of mature NCs (21,48,49). To test this possibility, we extracted HBV core DNA in the absence of exogenous nuclease digestion of the cytoplasmic lysate.…”
Section: Resultssupporting
confidence: 74%
“…1 and 2 (see Materials and Methods), the putative unstable mature NCs formed by the mutant core proteins, which might have been accumulated in the cells, could have been eliminated as a result of the nuclease digestion. This possibility was supported by previous studies by us and others showing that certain capsid mutations of DHBV can indeed lead to preferential destabilization of mature NCs (21,48,49). To test this possibility, we extracted HBV core DNA in the absence of exogenous nuclease digestion of the cytoplasmic lysate.…”
Section: Resultssupporting
confidence: 74%
“…In support of the latter view, Gazina et al found no significant impact of site-specific mutations within the DHBV core C terminus on pgRNA packaging (8). Further, previous work on mutations of the DHBV core C terminus has revealed a destabilizing effect at a later stage of nucleocapsid maturation, with selective nuclease sensitivity of capsid-associated rcDNA but not ssDNA (15,16). It should be noted, however, that mutational studies introduce permanent modifications that cannot reflect dynamic changes in the phosphorylation state during nucleocapsid assembly and disassembly.…”
Section: Discussionsupporting
confidence: 51%
“…In a recent study it was shown that DHBV core protein mutants lacking parts of the C-terminal basic domain or carrying an alanine or aspartate residue instead of one of the phosphorylatable serines formed capsids that rendered rcDNA selectively sensitive to nuclease. Hence, its absence from nuclease-treated samples was not caused by a defect in DNA synthesis but by the inability of the mutant capsid structure to effectively shield the DNA from nuclease attack (14,15).…”
mentioning
confidence: 99%
“…Since an accumulative effect in the inhibition mediated by the p300(S384A) mutant and A238L was not observed, it can be proposed that A238L might block the phosphorylation of serine 384, thus supporting the hypothesis that involves this serine in the A238L-mediated inhibition. To further confirm this hypothesis, we generated mutant constructs of p300 in which serine 384 has been substituted by aspartic acid, which is a phosphoserine mimicking substitution that can produce constitutively active mutants (37). The S384D mutant construct was then used in experiments similar to those described above, showing that in ASFVinfected Vero cells, the ectopic expression of the S384D mutant construct not only reversed the inhibition induced by the A238L protein (expressed during the Ba71Vwt virus infection) on the activity of the COX-2 (Fig.…”
Section: Vol 83 2009 A238l Inhibits P300-mediated Inflammatory Respmentioning
confidence: 99%